A surveillance-based epidemiological study of renal agenesis in 25 million births in china, 2007–2020 - Yuyang Gao; Wenli Xu; Wenyan Li; Zhiyu Chen; Qi Li; Zhen Liu; Li Dai (BMC Pregnancy and Childbirth)
Abstract Background Renal agenesis (RA), a rare congenital kidney defect, varies in clinical severity. Unilateral renal agenesis (URA) is more prevalent and may cause long-term renal complications, whereas bilateral renal agenesis (BRA) is typically fatal. While epidemiological data on RA is limited in China, understanding its prevalence and associated factors is crucial for public health interventions. Methods We conducted a prevalence analysis using data from the Chinese Birth Defects Monitoring Network between 2007 and 2020. Prevalence rates of RA, URA, and BRA were calculated and stratified by birth year, maternal age, residence area, geographical region, and infant sex. Temporal trends in prevalence were examined. We also investigated pregnancy outcomes among affected infants, including preterm births, low birth weight, early neonatal deaths, and termination of pregnancy for fetal anomaly (TOPFA). Furthermore, co-occurring congenital anomalies were assessed. Poisson regression analysis was used to assess the distribution of URA and BRA across residential areas and geographic regions and to identify factors associated with their prevalence. Results Among 25,909,000 births between 2007 and 2020, a total of 5,906 cases of RA were identified (5,020 URA and 780 BRA). The prevalence rates per 10,000 live and still births were 2.28 for RA, 1.94 for URA, and 0.30 for BRA, all showing an increasing trend over the study period. Compared to URA, BRA was significantly associated with a higher proportion of preterm birth, low birth weight, early neonatal death, and TOPFA. Poisson regression analysis revealed a consistent distribution of URA and BRA across residential areas and geographic regions, with higher prevalence observed in urban areas and the eastern and central regions of China. Maternal age < 35 years and female sex were associated with a higher prevalence of URA, while male sex was associated with a higher prevalence of BRA. Both URA and BRA frequently co-occurred with congenital malformations of the circulatory, urinary, and musculoskeletal systems. Conclusions The study provides the first comprehensive epidemiological assessment of RA in China. The increasing prevalence and distinct differences in the pregnancy outcomes between URA and BRA underscore the importance of timely prenatal diagnosis and appropriate counseling for affected families.